Performance of private equity-owned firms post-IPO - Lindberg, Marcus Carl Axel (2020)
This paper examines the effect of private equity involvement in initial public offerings. Two regression models were applied to assess the data ranging from 2006 and 2017 with IPOs on Nasdaq Stockholm. The dataset includes 126 firms out of which 33 were private equity-sponsored. The first regression model predicts next year’s return on assets with financials from the year prior to, and the year of the IPO. The second regression is using cumulative abnormal returns as dependent variable. Cumulative abnormal returns are computed for four different time windows following the event of the IPO, in order to measure the effect private equity firms have on companies they are backing in the event of an IPO. t can be concluded that private equity firms have a positive impact through their involvement, both in terms of return on assets and cumulative abnormal returns. However, the positive effect on cumulative abnormal returns can only be validated for the three-month period following the initial public offering.